2017
DOI: 10.1536/ihj.16-438
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Diuresis for Acute Decompensated Heart Failure by Tolvaptan

Abstract: SummaryTolvaptan, a vasopressin type 2 receptor antagonist, does not affect kidney circulation or cause worsening of renal function (WRF) in patients with acute decompensated heart failure (ADHF). Bioelectrical impedance analysis (BIA) can be used to evaluate intravascular volume by calculating the ratio of extracellular water (ECW) to intracellular water (ICW). There have been no reports examining the mechanisms of tolvaptan-induced diuresis using BIA. We investigated whether tolvaptan decreases excess volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…24) It is noteworthy that tolvaptan, a vasopressin V2 receptor antagonist that suppresses the effect of AVP, has been reported to improve symptoms in patients with HF in the short-term. [25][26][27][28] This may be evidence supporting our results that the prognosis of patients with higher plasma AVP levels is poorer and that the suppression of AVP activity may lead to the improvement of the pathophysiological condition in patients with ADHF. More detailed analysis of the physiological activities of AVP and the pathogenesis of HF may expand the spectrum of available treatment options for ADHF.…”
Section: Discussionsupporting
confidence: 84%
“…24) It is noteworthy that tolvaptan, a vasopressin V2 receptor antagonist that suppresses the effect of AVP, has been reported to improve symptoms in patients with HF in the short-term. [25][26][27][28] This may be evidence supporting our results that the prognosis of patients with higher plasma AVP levels is poorer and that the suppression of AVP activity may lead to the improvement of the pathophysiological condition in patients with ADHF. More detailed analysis of the physiological activities of AVP and the pathogenesis of HF may expand the spectrum of available treatment options for ADHF.…”
Section: Discussionsupporting
confidence: 84%
“…With BIA, Nagayama et al demonstrated different effects on fluid distribution between tolvaptan and furosemide in a patient with liver cirrhosis and chronic kidney disease [38]. Nomoto et al showed that in patients with acute decompensated heart failure, diuresis due to tolvaptan caused no significant change of ECW/ICW ratio by using BIA, while that due to conventional diuretics decreased ECW/ICW ratio [11]. This finding suggested a net reduction of ICW might characterize tolvaptan from conventional diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…These factors are also common pathophysiological features of fluid control in hemodialysis patients due to chronic renal failure. Body composition and fluid status monitoring assessed by non-invasive BIA, especially intracellular water (ICW), have been shown to be of prognostic value in acute decompensated heart failure, [11] acute kidney injury under continuous hemodiafiltration, [12] and patients with chronic renal failure under hemodialysis [13,14]. Therefore, BIA has also been shown to be an applicable tool for assessment of ICW, even in patients with possible overhydration or vigorous fluid status changes.…”
Section: Introductionmentioning
confidence: 99%
“…Increased vasopressin levels and the use of loop diuretics can cause hyponatremia 34. Loop diuretics are commonly used in HF treatment;33,36,37 however, up to 30% of patients are resistant to this type of therapy. Other side effects of loop diuretic therapy include electrolyte imbalance or hypotension 34,37,38…”
Section: Tolvaptanmentioning
confidence: 99%
“…Urine volume is increased but there is no change in the excretion of electrolytes 3335,39. Studies show that tolvaptan increases serum sodium levels in patients with hyponatremia34,35,37,39 and has a lower tendency for worsening renal function than standard diuretics 36,38…”
Section: Tolvaptanmentioning
confidence: 99%